Inuit perspectives on research ethics: The work of Inuit Nipingit - Nickels, Scot; Knotsch, Cathleen (Études/Inuit/Studies, 2011)
In 2008, Inuit Tapiriit Kanatami and Inuit Tuttarvingat of the National Aboriginal Health Organization collaborated to provide input to national discussions of research ethics and processes in the Canadian Arctic. This paper describes the work of Inuit Nipingit (National Inuit Committee on Ethics and Research) during two years from 2008 to 2010. The Inuit Nipingit committee was concerned with research and its ethics environment as faced by Inuit as research participants, researchers, and those being consulted on research proposals. Members of this national committee discussed Canada’s ethical guidelines for research and responded to a call for input into the Tri-Council Policy Statement: Ethical Conduct for Research Involving Humans. In an effort to support capacity building, Inuit Nipingit also produced reference materials for Inuit community members and anyone concerned in research involving Inuit.